Forest Management Model Based on Community Participation Under the Provisions of Forestry Law in the KPH Saradan, Madiun, East Java - Eko Wahyudi; Anajeng Esri Edhi Mahanani; Rohmatul Faizah (Nusantara Science and Technology Proceedings)
This paper aims to analyze forest management by involving community participation in the field of legal policy in the KPH Saradan, Madiun, East Java. Furthermore, it will also be assessed the appropriate model for forest management in Indonesia, so that community participation-based in forest management becomes the appropriate alternative to resolve the forestry issues in Indonesia, specifically related to deforestation as a consequence of the weak legal policies. This research is part of socio-legal research. The type of data used in this research is primary and secondary data. As a result, it can be said that; First, forest management based on community participation is a KPH program named as the Community Forest Management, wherein Law Number 41 of 1999 on Forestry, Government Regulation of the Republic of Indonesia on Forest Management and Forming of Forest Management Plan, and Forest Utilization, also Community Forest Management Policy PLUS (PHBM Plus) as the legal basis. Second; the Forest management model based on community participation has not been implemented optimally yet. The obstacles that arise are precisely associated with the lack of control in management efforts. Community participation in managing forests without supervision will be a boomerang for forest sustainability in Indonesia. For this reason, creating a monitoring model is a key requirement in discussing the forest management model in Indonesia